Recurrence of extreme serum analytes in consecutive pregnancies and association with obstetrical outcomes. (2nd January 2019) - Soni, Shelly; Krantz, David A.; Greenberg, Meir; Vohra, Nidhi; Rochelson, Burton
Abstract: Objective: To evaluate if presence of extreme maternal serum biochemical analytes recurs in consecutive pregnancies. We hypothesized that presence of >1 extreme analyte in prior pregnancy is associated with increased risk of adverse pregnancy outcome in subsequent pregnancy. Methods: Retrospective cohort study of singleton pregnancies evaluated and delivered in 2 consecutive pregnancies (2011–2015). Adverse outcomes were defined as indicated preterm delivery before 37 completed weeks due to preeclampsia, fetal growth restriction or other complications. Results: First and second trimester maternal serum analytes were assessed in 1434 patients in 2 consecutive pregnancies. The presence of >1 extreme serum analyte in prior pregnancy significantly increased likelihood of >1 extreme analyte in subsequent pregnancy. The likelihood increased as number of prior extreme markers increased. In patients with normal outcomes and 2 or more extreme serum analytes in prior pregnancy, there was an increased incidence of adverse pregnancy outcomes in subsequent pregnancy with relative risk (RR) of 5.42 [95% CI 1.6–18.3]. Conclusions: The presence of more than 1 extreme serum marker in one pregnancy increases likelihood of recurrence in subsequent pregnancies. Risk of adverse outcomes in subsequent pregnancy can be evaluated based on biochemistry results as well as prior pregnancy outcomes.